A comparative study of Islamic religion education concept at songserm Islam seksa school pattani southern Thailand and Muhammadiyah Boarding School Yogyakarta Indonesia - Trias Setyo Putro (Fak. Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2016)
wt,1/nis,c.1